Teachers ’ Attitudes towards the Use of Arabic (L1) in primary EFL Classrooms in Iraq - Ali, Eman Rasheed (Al-Adab Journal, 2022)
Having recourse to learners’ mother tongue in foreign language (FL) classes has been a controversial topic in the field of teaching English as a foreign language for a long time. There has been a great deal of claims and counterclaims that revolve around the pedagogical appropriateness of teacher usage of learners’ mother tongue in foreign language teaching. Recently, the findings of English as a foreign language (EFL) research cast doubt on the rationales of proponents of exclusive use of FL in EFL setting; and researchers come up with the reality that a rational use of first language (L1) is not only inevitable but also profitable in classrooms where teachers and learners share the same L1. Dearth of knowledge on the pedagogical reality of this issue in Iraqi EFL contexts is worth exploring. This study aimed at highlighting English language teachers’ attitudes towards using the learners’ mother tongue (Arabic) in the EFL classrooms, seeking their viewpoints on the purposes for which Arabic could be used in English classes, and exploring their reasons for using it. For this end, the study was conducted on 50 EFL teachers teaching at public primary schools in Baghdad, using a questionnaire survey developed to fulfill the aim of the study. Findings of the obtained data demonstrate that teachers’ overall attitudes towards occasional use of Arabic in EFL classrooms were positive; and they reported using Arabic for both teaching and classroom management purposes. Analysis of the data also indicates that all of the participants were inclined to switch to Arabic in their EFL classrooms for a number of reasons necessary to create a more comprehensible, motivational, relaxing, friendly, and supportive classroom environment for young learners and to save time and effort in overcrowded classes.